Dispositionen: Segen oder Fluch für die kausale Theorie der epistemischen Stützungsbeziehung? - Mantel, Susanne (Zeitschrift für philosophische Forschung, 2017)
Many of our beliefs are based on other mental states. What does this basing relation consist in? Causal theories give the following causal condition for the belief B being based on the mental state M: (CC) M has caused B (or causes that B is maintained). The problem of deviant - causal chains shows that CC is not sufficient for the basing relation. It has been proposed to solve this problem by introducing the following further dispositional condition that, together with CC, gives necessary conditions for the basing relation: (DC) B is the manifestation of a cognitive - disposition of the subject to form beliefs similar to B if it is in states similar to M. I will explore whether DC improves causal theories or, to the contrary, weakens those theories. Although DC excludes deviant causal chains successfully it casts doubts on whether CC is a necessary - condition. As soon as DC is accepted, everything speaks in favor of abandoning CC. Thus, the attempt to improve causal theories by introducing a dispositional condition unintentionally challenges the causal approach and indicates that a purely dispositional theory is to be preferred.